Penerapan Model Problem Based Learning dalam Pembelajaran Logika dan Ushul Fiqh: Studi Kasus di Di Lembaga Akselerasi Logika Dan Ushul Fiqh (Logis) Pondok Pesantren Mammbaul Ulum Bata-Bata Panaan Palengaan Pamekasa - Ruslan, Mohammad (Al-Ridha: Jurnal Pengabdian kepada Masyarakat, 2023)
Model learning is very much, including the problem-based learning model. The problem-based learning model itself is a learning model in which there is a problem-solving process carried out by students, both individually and in groups. The PBL model has been carried out by the Institute for the acceleration of Logic and Ushul Fiqh (Logical) in the study of Logic and Ushul Fiqh. This study aims to find out how the application of the PBL model in the LOGIS acceleration institution, the impacts and obstacles faced in implementing the PBL model. This is very important to be studied as an effort to develop the PBL model. The research method used is a qualitative method with a discriminatory case study type. Researchers as full participants. The subjects of this study were the head of LOGIS, Head of Education Bid, some LOGIS supervisors, and some LOGIS members. and some members of LOGIS. Data collection is carried out by interview, observation and documentation techniques. The results showed that: the application of the problem-based learning model in learning Logic and Ushul Fiqh in the Logic and Ushul Fiqh (LOGICAL) acceleration lemabaga can be said to be good. This is still not said to be perfect because there are obstacles faced in implementing the PBL model itself.